Problem-solving analysis in solving HOTS problems judging from self-confidence - Azzahra, Luthfia; Nurhanurawati, Nurhanurawati (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study analyzes the process of solving students' mathematical problems based on Polya's level and self-confidence. This research is a type of qualitative research with a case study approach. The subjects used in this study consisted of three students representing the level of confidence. Data collection in this study was conducted using triangulation techniques, which included tests, non-tests, and interviews. The results of the study were obtained based on the Polya level: Students with a high level of confidence will understand the problem clearly, plan steps to solve it, implement the solution plan, and check the results obtained. Students with moderate confidence only understand the problem clearly and plan the solution steps. Students with low self-confidence can only meet a few levels of Polya. Therefore, students with a high level of confidence do not hesitate and maximize their potential in solving problems so that they can solve them.